CORE-CERT Items as a Minimal Requirement for Replicability of Exercise Interventions: Results From Application to Exercise Studies for Breast Cancer Patients. Issue 5 (28th May 2023) - Bünzen, Claudia; Knuth, Janina; Bucher, Marieke; Weisser, Burkhard; Schmidt, Thorsten
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Hacke, C, Knuth, J, Bucher, M, Weisser, B, and Schmidt, T. CORE-CERT items as a minimal requirement for replicability of exercise interventions: results from application to exercise studies for breast cancer patients. J Strength Cond Res 37(5): e346–e360, 2023—Exercise interventions have been demonstrated to be useful in the prevention and therapy for multiple different diseases. The Consensus on Exercise Reporting Template (CERT) has been developed as the reporting guideline for exercise studies. The main goals of CERT are to ensure completeness of reporting, to enable interpretation of exercise programs, and to allow extraction of data for meta-analyses and the development of guidelines. However, for clinicians, the most important aspect of good reporting might be the replicability of protocols for their patients. This study was designed to determine the core components of exercise interventions for breast cancer, which are considered as minimal requirement for replicability in practice. The original items of CERT were specified, subdivided, or extended by additional key items to develop a "CORE-CERT checklist." The original CERT and our CORE-CERT were then applied to 29 exercise RCTs for breast cancer obtained from the most frequently cited and most recent meta-analyses in current guidelines. The reporting quality using both templates were examined. Mean original CERT score was 11 of 19 (59%) of completed items and 13 of 19 (68%) of reporting completeness for CORE-CERT. Reporting quality using CORE-CERT items was approximately 8% higher, indicating a more precise description of items in CORE-CERT. Differences concerned exercise dosage, nonexercise components, supervision, and description of each exercise. We propose a novel CORE-CERT guideline necessary for the replicability of exercise interventions in clinical practice. The application of CORE-CERT demonstrated a slightly better but still insufficient reporting quality of exercise interventions for breast cancer.